Pengaruh Pelatihan, Kompensasi terhadap Kepuasan Kerja Karyawan dan Kinerja Karyawan - Supatmi, Mamik Eko; Nimran, Umar; Utami, Hamidah Nayati (FIA UB, 2013)
ABSTRACTTraining is an activity series designed to enhance skill, knowledge, experience, or an individualÂ attitude changes. Compensation research is one of the essential factors to job satisfaction and employee performance. Compensation is divided into financial compensation which consists of salary, performance payment, incentive payment, outside working hours payment, social protection and non-financial compensation with consists of work. Both of these elements will have an effect to increase employee satisfaction and performance. The important conclusions of this research are compensation to the employee is very important to improve customer satisfaction and employee performance environment working.Keywords: Training, Compensation, Employee Job Satisfaction and Performance environment working.ABSTRAKPelatihan adalah serangkaian aktifitas yang dirancang untuk meningkatkan keahlian-keahlian, pengetahuan, pengalaman, ataupun perubahan sikap seorang individu. Dalam penelitian kompensasi juga merupakan salah satu faktor yang dipengaruhi pada kepuasan kerja dan kinerja karyawan. Kompensasi terbagi menjadi kompensasi finansial terdiri dari gaji, bayaran prestasi, bayaran insentif, bayaran diluar jam kerja, program perlindungan dan kompensasi non finansial terdiri dari pekerjaan. Kedua unsur ini akan berpengaruh pada meningkatnya kepuasan dan kinerja karyawan. Data penelitian ini mendapatkan beberapa kesimpulan penting bahwa kompensasi sangat penting bagi karyawan dalam upaya meningkatkan kepuasan dan kinerja karyawan di lingkungan kerja.Kata Kunci: Pelatihan, Kompensasi,Kepuasan Kerja Karyawan dan Kinerja Karyawan.